Agmatine inhibits naloxone-induced contractions in morphine-dependent guinea pig ileum - ARICIOĞLU, FEYZA (NEW YORK ACAD SCIENCES, 2003)
This study investigates the effects of agmatine on naloxone-precipitated withdrawal syndrome in morphine-dependent guinea pig ileum. Male guinea pigs that were starved for 24 hours were decapitated after cervical dislocation, and terminal portions of the ilea were removed. Segments were fixed at a resting tension of 1 g in an organ bath containing 1 x 10(-6) M morphine in Tyrode solution at 37 degreesC, which was bubbled with 95% O-2 and 5% CO2. Tissues were incubated in morphine containing Tyrode solution for 4 hours before agmatine was added. Naloxone and agmatine had no effect on naive ilea. Naloxone (1 X 10-6 M) contracted morphine-dependent ilea. Agmatine significantly inhibited the contractile response to naloxone in a dose-dependent manner (1 X 10(-7) M, 44%; 1 x 10(-6) M, 80%; 1 x 10(-5) M, 95%). This effect of agmatine was partly abolished by pretreatment with yohimbine and was almost completely abolished by idazoxan.
Keywords: agmatine; morphine; imidazoline; alpha(2)-adrenergic; NMDA; nitric oxide; ileum; NITRIC-OXIDE SYNTHASE; L-ARGININE; PHYSICAL-DEPENDENCE; ABSTINENCE SYNDROME; TOLERANCE; WITHDRAWAL; CLONIDINE; RATS; ATTENUATION; RECEPTORS